Школа игры на шестиструнной гитаре: учебное пособие / П. Агафошин ; ред. Е. Ларичев - Агафошин П. (Музыка, 1990)
Экземпляры: ф.10 (20180320) / Инвентарный номер: 22152 / Сис.шифр: 85.956.4 / Авт.знак: А 23 / ББК: 85.956.419.1